2004
DOI: 10.1167/iovs.03-0265
|View full text |Cite
|
Sign up to set email alerts
|

Test–Retest Reliability of Clinical Shack-Hartmann Measurements

Abstract: Increased variability in aberration maps between days and months indicates biological fluctuations that are large enough to prevent achievement of "perfect vision," even in the unlikely event that spherical and astigmatic refractive errors are corrected perfectly. However, lack of stability does not justify withholding treatment. A lasting benefit of aberration correction is expected despite temporal variability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
89
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(93 citation statements)
references
References 32 publications
2
89
2
Order By: Relevance
“…The variability that we measured for higher-order aberrations was only slightly worse that that reported by Cheng et al (2004) They estimated that most of the COAS' variability was attributable to fluctuations in accommodation, the tear film or eye position rather than due to the instrument itself. The COAS may be subject to axial, transverse or angular positioning errors, but they demonstrated that, within the range of misalignments expected for normal clinical use, these caused no significant error.…”
Section: Repeatabilitycontrasting
confidence: 77%
“…The variability that we measured for higher-order aberrations was only slightly worse that that reported by Cheng et al (2004) They estimated that most of the COAS' variability was attributable to fluctuations in accommodation, the tear film or eye position rather than due to the instrument itself. The COAS may be subject to axial, transverse or angular positioning errors, but they demonstrated that, within the range of misalignments expected for normal clinical use, these caused no significant error.…”
Section: Repeatabilitycontrasting
confidence: 77%
“…Using retinal IQMs to relate objective measures of visual performance to those subjectively achieved is of particular interest [9][10][11]. Since the optical system of the eye is assumed to be linear, the retinal image quality assessment can be essentially reduced to the comparison of the diffraction limited point spread function (PSF) and the actual aberrated PSF or their respective Fourier transformations, the Optical Transfer Functions (OTFs).…”
mentioning
confidence: 99%
“…These metrics were included in the performance analysis as they showed, in several studies [9,11], good correlation with subjective visual performance.…”
mentioning
confidence: 99%
“…Both approaches generate accurate and precise measurements of lower and higher order monochromatic aberrations, 29,33,11 and we used both to compare the on-and off-eye aberrations of defocus and spherical aberration observed over a wide dioptric range of three hydrogel and two silicone hydrogel contact lenses. The wet cell provides neutral buoyancy and stable hydration, and thus largely avoids the mechanical forces and hydration fluctuations that might be present when on the eye.…”
Section: Discussionmentioning
confidence: 99%